Development of Bovine Gastric Organoids as a Novel In Vitro Model to Study Host-Parasite Interactions in Gastrointestinal Nematode Infections - Faber, Marc N.; Smith, David; Price, Daniel R. G.; Steele, Philip; Hildersley, Katie A.; Morrison, Liam J.; Mabbott, Neil A.; Nisbet, Alasdair J.; McNeilly, Tom N. (Frontiers in Cellular and Infection Microbiology, 2022)
Gastro-intestinal nematode (GIN) parasites are a major cause of production losses in grazing cattle, primarily through reduced growth rates in young animals. Control of these parasites relies heavily on anthelmintic drugs; however, with growing reports of resistance to currently available anthelmintics, alternative methods of control are required. A major hurdle in this work has been the lack of physiologically relevant in vitro infection models that has made studying precise interactions between the host and the GINs difficult. Such mechanistic insights into the infection process will be valuable for the development of novel targets for drugs, vaccines, or other interventions. Here we created bovine gastric epithelial organoids from abomasal gastric tissue and studied their application as in vitro models for understanding host invasion by GIN parasites. Transcriptomic analysis of gastric organoids across multiple passages and the corresponding abomasal tissue showed conserved expression of tissue-specific genes across samples, demonstrating that the organoids are representative of bovine gastric tissue from which they were derived. We also show that self-renewing and self-organising three-dimensional organoids can also be serially passaged, cryopreserved, and resuscitated. Using Ostertagia ostertagi, the most pathogenic gastric parasite in cattle in temperate regions, we show that cattle gastric organoids are biologically relevant models for studying GIN invasion in the bovine abomasum. Within 24 h of exposure, exsheathed larvae rapidly and repeatedly infiltrated the lumen of the organoids. Prior to invasion by the parasites, the abomasal organoids rapidly expanded, developing a ‘ballooning’ phenotype. Ballooning of the organoids could also be induced in response to exposure to parasite excretory/secretory products. In summary, we demonstrate the power of using abomasal organoids as a physiologically relevant in vitro model system to study interactions of O. ostertagi and other GIN with bovine gastrointestinal epithelium.